Motivasi Bertani Petani Milenial di Kecamatan Tulung, Kabupaten Klaten - Misbah, Noor Kalimatul; Lestari, Eny; Suminah, Suminah (Universitas Sebelas Maret, 2025)
Farming Motivation of Millennial Farmers in Tulung Sub-District, Klaten Regency. Indonesia’s agricultural sector has faced a crisis in the regeneration of millennial farmers. Based on data from the Agricultural Extension Center (BPP) of Tulung Sub-district in 2022, there are only 323 farmers from the age range of 22 to 37 years, which accounts for only 2% of the total millennial generation involved in agriculture. The farming motivation of millennial farmers plays a crucial role in the regeneration process of farmers in Indonesia. With high motivation, the regeneration of farmers can be achieved more effectively. This study aims to describe and analyze the factors that influence the farming motivation of millennial farmers. The unit of analysis in this study is millennial farmers with specific criteria in six villages in Tulung Sub-district, Klaten Regency. The sample consists of 53 respondents selected using the proportional random sampling method, determined through the Slovin formula. The data were analyzed using Multiple Linear Regression with the Ordinary Least Square (OLS) method, facilitated by the IBM SPSS Statistics 27 application and Shazam version 9.0. The results showed that the role of agricultural extension agents, non-formal education, land tenure area, farming experience, and government program support collectively explained 70.42% of the variance in farming motivation among millennial farmers in Tulung Sub-district. Variables that positively and significantly influence the farming motivation of millennial farmers include the role of agricultural extension agents, non-formal education, land tenure area, and farming experience. Conversely, government program support has a negative and significant effect, likely due to the perceived abundance of programs that are not effectively implemented or aligned with the needs of millennial farmers. Therefore, it is imperative to design more tailored and equitable government programs, accompanied by regular evaluations, to encourage and support millennial farmers effectively.